Estimating regional differences in returns to education when schooling and location are determined endogenously - Tuomo Suhonen; Jaakko Pehkonen; Hannu Tervo (European Regional Science Association (ERSA), 2010)
While the growing supply of university skills is known to have agglomerated towards the large centers in Finland, there is no research knowledge available on the development of regional demands. This paper attempts to fill this gap by analyzing regional variation in the private-sector return to university education in Finland for the period 1970 - 2004. In the analysis, we focus on studying 1) whether there are differences in the return to university between different region types, and 2) to what extent can these differences - if they exist - be explained by differences in regional skill supply and unemployment. For the econometric analysis, we use a large register-based dataset constructed by Statistics Finland and an estimation strategy that takes into account the possible nonlinearities in the effects of the regional variables, as well as biases arising from sample selection and endogeneity of education.
Keywords: C14; C31; J24; J31; 330; returns to education; regional differences; sample selection models; nonparametric estimation